Inhibitory Effect of Isolated Bacteria from the Phycosphere of Levanderina fissa on the Growth of Different Microalgae - Tang, Yali; Xie, Changliang; Jin, Xiaotong; Wang, Zhaohui; Hu, Ren (Frontiers in Marine Science, 2022)
Levanderina fissa (formerly Gyrodinium instriatum) frequently causes blooms in the Pearl River Estuary and has few advantages in interspecific competition with other bloom-forming algal species. Phycosphere bacteria, which closely interact with algal cells, may play an ecologically functional role in the population dynamics and bloom occurrence. To test this hypothesis, we isolated and identified cultivable bacteria coexisting in different growth stages of L. fissa by the gradient dilution method and investigated the characteristics of the bacterial interactions with three diatom species (Chaetoceros curvisetus, Skeletonema dohrnii, and Phaeodactylum tricornutum) and three dinoflagellate species (Scrippsiella acuminata, Karenia mikimotoi, and the host algae) after screening for functional bacteria. One of the isolated bacterial strains, Lf7, which was phylogenetically identified as an Alteromonas species, showed significant inhibitory effects on different algal species except its host. Moreover, all algal species, especially their hosts, showed significant stimulatory effects on bacterial Lf7 growth. These results indicate that the phycosphere bacterium Lf7 may play some ecological roles in the competition between its host alga L. fissa and other phytoplankton. The study also highlights the complicated interactions between phycosphere bacteria and host algae.